Indentation-induced two-way shape-memory effect in aged Ti-50.9 at.% Ni. (2nd January 2015) - Frensemeier, Mareike; Arzt, Eduard; Qin, Enwei; Frick, Carl P.; Schneider, Andreas S.
Abstract: Abstract : In this study, Vickers indentation was used to investigate the two-way shape-memory effect (TWSME) in an austenitic Ti-50.9 at.% Ni alloy, exposed to different heat treatments. Three aging treatments were used to manipulate the size of Ti3 Ni4 precipitates. All samples were Vickers indented, and the indent depth was investigated as function of thermal cycling. The TWSME was found only in the material aged at 400 °C, which contained coherent precipitates. Thermal cycling shows stable TWSME, however, heating well above the austenite finish temperature lead to permanent austenitic protrusions. The results indicate that stabilized martensite plays a critical role in creating TWSME surfaces.